Achieving healthy aging through gut microbiota-directed dietary intervention: Focusing on microbial biomarkers and host mechanisms - Yue Xiao; Yingxuan Feng; Jianxin Zhao; Wei Chen; Wenwei Lu (Journal of Advanced Research)
Background: Population aging has become a primary global public health issue, and the prevention of age-associated diseases and prolonging healthy life expectancies are of particular importance. Gut microbiota has emerged as a novel target in various host physiological disorders including aging. Comprehensive understanding on changes of gut microbiota during aging, in particular gut microbiota characteristics of centenarians, can provide us possibility to achieving healthy aging or intervene pathological aging through gut microbiota-directed strategies. Aim of Review: This review aims to summarize the characteristics of the gut microbiota associated with aging, explore potential biomarkers of aging and address microbiota-associated mechanisms of host aging focusing on intestinal barrier and immune status. By summarizing the existing effective dietary strategies in aging interventions, the probability of developing a diet targeting the gut microbiota in future is provided. Key Scientific Concepts of Review: This review is focused on three key notions: Firstly, gut microbiota has become a new target for regulating health status and lifespan, and its changes are closely related to age. Thus, we summarized aging-associated gut microbiota features at the levels of key genus/species and important metabolites through comparing the microbiota differences among centenarians, elderly people and younger people. Secondly, exploring microbiota biomarkers related to aging and discussing future possibility using dietary regime/components targeted to aging-related microbiota biomarkers promote human healthy lifespan. Thirdly, dietary intervention can effectively improve the imbalance of gut microbiota related to aging, such as probiotics, prebiotics, and postbiotics, but their effects vary among.